Caminos ocultos - O'Dell, Tawni (Nuevos tiempos (Madrid, Spain), 2012)
A novel on a dysfunctional family in a Pennsylvania coal-mining town. The mother is in jail for killing the father and the four children are on their own. They are supported by the eldest, Harley Altmyer, 20, who is having an affair with the mother of a friend of his sister.